Dampak Perubahan Mekanisme Perhitungan Pajak Penghasilan PPh 21 Bagi Cash Flow Perusahaan (Studi Kasus Wajib Pajak Perusahaan) - Hanapiah, Hanapiah; Bulan, Sri; Humaimah, Sunni; Sugiyanto, Sugiyanto (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study investigates the impact of the new calculation mechanism of Article 21 Income Tax (PPh 21), particularly the application of the Average Effective Rate (TER), on corporate cash flow. While prior studies have discussed compliance and tax administration reform, limited attention has been given to how regulatory changes affect companies that provide tax allowances to employees. This research aims to fill that gap by analyzing the financial implications for a case company in the insurance sector. Using a qualitative descriptive approach, data were collected through document analysis, including company payroll and tax calculation reports, supported by relevant regulations such as PER-16/PJ/2016, PP No. 58/2023, and PMK 168/2023. The results show that the TER mechanism increases the tax burden for January to November, while in December the company experiences overpayment. A comparison between TER and the progressive tax method reveals that both lead to the same total annual liability, yet with different monthly cash flow impacts. The findings provide practical insights for companies in designing tax planning strategies to mitigate regulatory changes and strengthen financial management.